Thermophile mats of microalgae growing on the woody structure of acooling tower of a thermoelectric power plant in Central Mexico - Yadiralia Covarrubias; Enrique A. Cantoral-Uriza; J. Sergio Casas-Flores; J. Viridiana García-Meza (Revista Mexicana de Biodiversidad)
The aims of this research are to identify and describe a periphyton community of thermophilic microalgae in order to expand our knowledge onbiodiversity of a particular environment. Conspicuous biomass of thermophilic microalgae (48◦C) inhabits the cooling towers of the thermoelectricpower plant of Villa de Reyes (Central Mexico). Aggregate samples or microalgal mats were taken in three different areas of the top of a cooling tower,for identification. According to the sequencing analysis of 16S and 18S rDNA genes, the community is dominated by 3 species of Cyanoprokaryota:Chlorogloeopsis fritschii, Arthronema africanum and Chroococcidiopsis sp., previously reported as thermophiles. Also, 2 species of the Chlorophyteor green algae Scenedesmus. Finally, 12 species of diatoms comprise the microalgal community; diatoms were only microscopically identifiedwithin the mats, suggesting that the mats constitute a suitable microenvironment in thermal ambiences. The identified species are of particularinterest because their habitat represents an extreme and an artificial biotope. To the best of our knowledge, this is the first report of thermophiliccommunities of microalgae in Mexico from a power plant; also, this is the first report of A. africanum for the country.